FeCoNi-based amorphous alloy and preparation method and application thereof

Through the preparation of FeCoNi-based amorphous alloy, the unstable performance problem of existing amorphous alloys in extreme environments is solved, and high hardness, good magnetic properties and excellent corrosion resistance are achieved, which are suitable for applications in complex and harsh environments.

CN119685652APending Publication Date: 2025-03-25杭州极弱磁场国家重大科技基础设施研究院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840032.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The amorphous properties of existing amorphous alloys in extreme environments are unstable, and their microhardness, soft magnetic properties and corrosion resistance are poor, limiting their application in complex and harsh environments.

Method used

A FeCoNi-based amorphous alloy is used with the chemical formula (Fe1/3Co1/3Ni1/3)80-xSi6B14Yx, where the value of x is 0.5-4. Through specific smelting and quenching processes, an amorphous alloy with uniform composition and excellent properties is prepared.

Benefits of technology

The performance stability of FeCoNi-based amorphous alloy in extreme environments has been achieved, and its microhardness, soft magnetic properties and corrosion resistance have been improved. It is suitable for applications such as metal structural parts, magnetic core materials and protective coatings in marine engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685652A_ABST
    Figure CN119685652A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of amorphous alloys, in particular to a FeCoNi-based amorphous alloy and a preparation method and application thereof. According to the FeCoNi-based amorphous alloy provided by the invention, the chemical formula of the FeCoNi-based amorphous alloy is (Fe < 1 / 3 > Co < 1 / 3 > Ni < 1 / 3 >) < 80-x > Si < 6 > B < 14 > Y < x >, and the value range of x is 0.5-4. Iron, nickel and cobalt with the equal atomic ratio are used as main element materials, so that the amorphous alloy has magnetism, and the high-temperature performance and the corrosion resistance of the alloy material can be improved; boron and silicon are added into a principal element material, so that the alloy material is promoted to be converted into an amorphous structure, and the hardness and strength of the alloy are improved; the rare earth element Y with the large atomic radius is selected, melt can be purified, the microstructure can be improved, and the prepared amorphous alloy not only has high hardness and corrosion resistance, but also has high stability at the high temperature and can still show the amorphous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of amorphous alloys, and in particular to a FeCoNi-based amorphous alloy and a preparation method and application thereof. Background Art

[0002] Precision alloy refers to alloys with special physical properties. It is an indispensable material in the electrical industry, electronic industry, precision instrument industry and automatic control system. Alloys with excellent magnetic properties and corrosion resistance are widely used in automobiles and other industrial and consumer fields, such as automobile fuel injection devices, oil pump motor laminations, ABS systems and suspension automatic adjustment systems, and solenoid valves of various types of equipment such as refrigerators, washing machines, and vending machines. They can also be used for any electromagnetic components exposed to light chemical media. With the application requirements of various corrosive environments, soft magnetic alloys, as one of the most important precision alloys, need to have not only soft magnetic properties, but also good corrosion resistance. For example, automobile fuel injection devices must resist corrosion caused by fuel containing methanol / ethanol, and other application conditions must resist corrosion from harsh aqueous solutions, especially crevice corrosion of solenoid valves caused by chloride ions. The 21st century is the "century of the ocean". The development of marine affairs has become a broad consensus around the world, and the rational development and utilization of marine resources is a topic of common concern to countries around the world. At the same time, the research and application of high-performance corrosion-resistant functional materials have become a hot spot pursued by the current industry, and the development of advanced alloy materials with multiple functional characteristics has become more urgent.

[0003] Amorphous alloys were first obtained by Professor Duwez of the United States in the 1960s through melt spinning. Compared with traditional metal alloys, they have unique microstructures, with long-range atomic arrangement in a disordered state and short-range ordered state. Compared with crystalline materials, amorphous alloys do not have defects such as dislocations and grain boundaries, so they exhibit excellent mechanical properties (such as high strength, high hardness, good wear resistance), as well as excellent corrosion resistance, soft magnetic properties, catalytic properties, etc. These characteristics make amorphous alloys widely used in electronics, automobiles, military industry, aerospace and other fields. Multi-principal alloys include medium-entropy alloys or high-entropy alloys, which are composed of a variety of main elements with a content of between 5% and 35%. It is a new material developed based on "chemical disorder", which breaks through the limitations of traditional alloy material primitives, innovatively develops and studies alloy materials from the perspective of entropy, and creates a new research field for metal materials. In addition, adding trace or small amounts of certain secondary elements to multi-principal alloys can also change the properties of the multi-principal alloy matrix, thereby further expanding the candidate alloy composition.

[0004] Amorphous alloys are mostly characterized by "single principal element" or "dual principal element" characteristics, while multi-principal element alloys obviously advocate the concept of "multi-principal element". Based on the design concepts of multi-principal element alloys and amorphous alloys, the research group of Academician Wang Weihua of the Institute of Physics of the Chinese Academy of Sciences first proposed the concept of multi-principal element amorphous alloys (i.e. medium / high entropy amorphous alloys) in 2011, combining the performance characteristics of "chemical disorder" of multi-principal element alloys and "structural disorder" of amorphous alloys. At the same time, they prepared bulk multi-principal element amorphous alloys Zn with disordered structures and exhibiting thermoplastic deformation behaviors similar to polymers at room temperature. 20 Ca 20 Sr 20 Yb 20 (Li 0.55 Mg 0.45 ) 20 Soon after, Takeuchi et al. from Tohoku University in Japan prepared a multi-principal amorphous alloy Pd containing both metal and non-metal elements. 20 Pt 20 Cu 20 Ni 20 P 20 In recent years, experts in the field of materials at home and abroad have conducted preliminary research on this type of material, deepened their understanding of its basic properties, and broadened the scope of use of multi-principal amorphous alloys as a functional material.

[0005] However, the amorphous properties of the amorphous alloys currently under development are unstable in extreme environments, which limits the application of amorphous alloy materials in complex and harsh environments. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defect of unstable amorphous properties of amorphous alloys in the prior art under extreme environments, thereby providing a FeCoNi-based amorphous alloy and a preparation method and application thereof.

[0007] Another technical problem to be solved by the present invention is to overcome the defects of poor microhardness, soft magnetic properties and corrosion resistance of amorphous alloys in the prior art, thereby providing a FeCoNi-based amorphous alloy and a preparation method and application thereof.

[0008] To this end, on the one hand, the present invention provides a FeCoNi-based amorphous alloy, the chemical formula of the FeCoNi-based amorphous alloy is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 80-x Si6B 14 Y x , where the value of x ranges from 0.5 to 4.

[0009] Preferably, the value range of x is 1-4.

[0010] In some embodiments, the amorphous alloy has a thickness of 25-40 μm and a width of 1-2 mm.

[0011] On the other hand, the present invention provides a method for preparing a FeCoNi-based amorphous alloy, comprising the following steps: mixing iron, cobalt, nickel, silicon, boron and yttrium according to a ratio to obtain a mixture; smelting the mixture in an inert atmosphere to obtain an intermediate; and quenching the intermediate in an inert atmosphere to obtain the amorphous alloy.

[0012] In some embodiments, the melting method includes at least one of induction melting or arc melting.

[0013] In order to ensure uniform distribution of the components in the master alloy ingot and avoid excessive difference in the content of the components per unit volume, in some embodiments, the mixed material is smelted at least 3 times, preferably 3-5 times.

[0014] In some embodiments, the quenching temperature is 1300-1500°C.

[0015] In some embodiments, the cooling rate of the quenching is greater than or equal to 10 5 K / s, a high cooling rate is conducive to the rapid cooling and solidification of alloy materials, and the preparation of amorphous composites of different forms is usually carried out by atomization method or vacuum belt spinning process. The cooling rates of these two processes can meet the requirements of the cooling rate of the present invention. The vacuum belt spinning process is used to prepare amorphous alloy strips, and its cooling rate can reach 10 5 K / s or more, preferably 10 5 K / s~10 6 K / s, especially by adopting high vacuum single-roll spinning quenching belt technology to prepare amorphous alloy strips, the large size difference between the atoms of each element and the rapid cooling process of single-roll spinning belt can make the metal atoms arranged in a disordered state and more easily form an amorphous structure.

[0016] Preferably, the cooling step includes spraying the molten alloy liquid onto the surface of the metal roller, and the surface linear speed of the metal roller is 25-40 m / s.

[0017] In some embodiments, the smelting vacuum degree is 4.0×10 -3 Pa~5.0×10 -3 Pa.

[0018] In order to ensure that all the elements can be completely melted, the melting current in the arc melting process is 180-250A, and the single melting time is 4-7 minutes.

[0019] In some embodiments, the intermediate body is quenched by induction coil melting.

[0020] In some of the embodiments, the atomic ratio of iron, cobalt, nickel, silicon, boron and yttrium is 25-27:25-27:25-27:6:14:0.5-4.

[0021] In some of the embodiments, before mixing the iron, cobalt, nickel, silicon, boron and yttrium, the surface of each raw material is polished and cleaned. The cleaning includes ultrasonic treatment, the cleaning agent is acetone or ethanol, and the number of cleaning times is 1-3 times.

[0022] Furthermore, the FeCoNi-based amorphous alloy provided by the present invention or the amorphous alloy prepared by the preparation method of the FeCoNi-based amorphous alloy is used in metal structural parts, magnetic core materials and protective coatings in marine engineering.

[0023] The technical solution of the present invention has the following advantages:

[0024] 1. The FeCoNi-based amorphous alloy provided by the present invention has a chemical formula of (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 80-x Si6B 14 Y x , wherein the value range of x is 0.5-4. The present invention uses iron, nickel and cobalt in equiatomic ratios as main materials, which can not only maximize the high entropy of the alloy, but also has the best thermal stability of the equiatomic main materials. In addition, high melting point nickel with corrosion resistance and ferromagnetism, and ferromagnetic materials iron and cobalt with high hardness and good wear resistance are used to make the amorphous alloy magnetic and improve the high temperature performance and corrosion resistance of the alloy material. At the same time, by adding boron and silicon with an atomic ratio of 3:7 to the main materials, the alloy material is promoted to be converted into an amorphous structure, and the hardness and strength of the alloy are increased. Furthermore, by selecting the rare earth element Y with a large atomic radius, not only the melt can be purified, but also the microstructure can be improved.

[0025] The FeCoNi-based amorphous alloy provided by the present invention increases the atomic radius difference of the main material (the atomic radius of Fe is 121.1pm, the atomic radius of Ni is 124.6pm, and the atomic radius of Co is 125.3pm) by adding different atomic radius elements Y, Si and B (the atomic radius of Y is 181.0pm, the atomic radius of Si is 115.3pm, and the atomic radius of B is 82.0pm), so that the alloy is more likely to present an amorphous structure, avoid structural defects such as dislocations and twins, and have an amorphous structure or a two-phase structure composed of an amorphous structure and a crystallized phase. It not only has high hardness and corrosion resistance, but also has strong stability at high temperatures and can still present an amorphous structure.

[0026] 2. The present invention provides a method for preparing a FeCoNi-based amorphous alloy, comprising the following steps: mixing iron, cobalt, nickel, silicon, boron, and yttrium according to a ratio to obtain a mixture; melting the mixture in an inert atmosphere by arc melting or induction melting to obtain an intermediate; melting, cooling, and forming the intermediate in an inert atmosphere. The present invention melts each raw material into an intermediate, and the FeCoNi-based amorphous alloy can be obtained by melting and cooling. The preparation process is simple and easy, the process is easy to control, and the obtained amorphous alloy has uniform composition and takes into account soft magnetic properties, corrosion resistance, microhardness, and high thermal stability.

[0027] 3. The preparation method of the FeCoNi-based amorphous alloy provided by the present invention, the smelting current in the arc smelting process is 180-250A, and the single smelting time is 5-7min. On the one hand, if the smelting current is too small, the element particles cannot be completely melted. On the other hand, if the smelting current is too large, light elements such as Si or B elements will splash and cause element loss. The present invention controls the smelting current between 180-250A to ensure that the element particles are melted without causing element loss.

[0028] 4. In the method for preparing the FeCoNi-based amorphous alloy provided by the present invention, the mixed material is smelted at least 3 times, preferably 3-5 times. The present invention can further improve the uniformity of each raw material in the alloy material by repeating the smelting times of the mixed material, and avoid unstable performance caused by uneven composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 is the XRD diagram of the FeCoNi-based amorphous alloy obtained in Examples 1-5 of the present invention;

[0031] Figure 2 is a SEM image of the FeCoNi-based amorphous alloy obtained in Examples 1-5 of the present invention, Figure 2 a in the formula represents the amorphous alloy obtained in Example 1, Figure 2 b in the figure represents the amorphous alloy obtained in Example 2, Figure 2 c in the figure represents the amorphous alloy obtained in Example 3, Figure 2 d in represents the amorphous alloy obtained in Example 4, Figure 2 e in which represents the amorphous alloy obtained in Example 5;

[0032] Figure 3 is a differential scanning calorimetry graph of the FeCoNi-based amorphous alloys prepared in Examples 1-5 of the present invention;

[0033] Figure 4 is a microhardness diagram of the FeCoNi-based amorphous alloys prepared in Examples 1-5 of the present invention;

[0034] Figure 5 is the hysteresis loop of the FeCoNi-based amorphous alloy obtained in Examples 1-5 of the present invention;

[0035] Figure 6 is a relationship diagram between the saturation magnetization and the coercive force of the FeCoNi-based amorphous alloys prepared in Examples 1-5 of the present invention;

[0036] Figure 7 It is a potentiodynamic polarization curve diagram of the FeCoNi-based amorphous alloy prepared in Examples 1-5 of the present invention. DETAILED DESCRIPTION

[0037] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0038] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0039] Example 1

[0040] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0041] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) are selected as raw materials, the oxide scale is polished and then ultrasonically cleaned with acetone or alcohol, and a high-precision balance with an accuracy of 0.001g is used for mixing the ingredients, wherein 8.949g of iron particles, 9.443g of cobalt particles, 9.405g of nickel particles, 1.019g of silicon fragments, 0.915g of boron fragments and 0.269g of yttrium blocks are used.

[0042] (2) Repeat the vacuum three times until the pressure in the furnace reaches 4.5×10 -3Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 230A for 5 minutes to prepare a master alloy ingot by arc smelting. During the smelting, cooling water is used to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 4 times for a total of 20 minutes to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79.5 Si6B 14 Y 0.5 The actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was found to be 7.380 g / cm 3 .

[0043] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79.5 Si6B 14 Y 0.5 The alloy particles were crushed into single 2-3g alloy particles. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt spinning machine. The vacuum degree in the furnace chamber was pumped to 4.0×10 -3 Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1400℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain the alloy strip, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79.5 Si6B 14 Y 0.5 The thickness of the multi-principal amorphous alloy strip is 30±8 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 40 m / s.

[0044] Example 2

[0045] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0046] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) are selected as raw materials, the oxide scale is polished and then ultrasonically cleaned with acetone or alcohol, and the ingredients are mixed using a high-precision balance with an accuracy of 0.001g, wherein 8.865g of iron particles, 9.355g of cobalt particles, 9.317g of nickel particles, 1.016g of silicon fragments, 0.912g of boron fragments and 0.536g of yttrium blocks are mixed.

[0047] (2) Repeat the vacuum three times until the pressure in the furnace reaches 4.5×10 -3 Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 230A for 5 minutes to prepare a master alloy ingot by arc smelting. During the smelting, cooling water is used to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 4 times for a total of 20 minutes to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 Y1, the actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was 7.289 g / cm 3 .

[0048] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 Y1 was crushed into single alloy particles of 2-3g. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt-spinning machine. The vacuum degree in the furnace chamber was drawn to 4.0×10 -3 Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1400℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain the alloy strip, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 The thickness of the Y1 multi-principal amorphous alloy strip is 30±8 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 40 m / s.

[0049] Example 3

[0050] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0051] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) are selected as raw materials, the oxide scale is polished and then ultrasonically cleaned with acetone or alcohol, and a high-precision balance with an accuracy of 0.001g is used for mixing the ingredients, wherein 8.698g of iron particles, 9.179g of cobalt particles, 9.142g of nickel particles, 1.009g of silicon fragments, 0.907g of boron fragments and 1.065g of yttrium blocks are used.

[0052] (2) Repeat the vacuum three times until the pressure in the furnace reaches 4.5×10 -3 Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 230A for 5 minutes, and a master alloy ingot is prepared by an arc smelting method to complete one smelting. During the smelting, cooling water is passed to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 4 times for a total of 20 minutes to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 78 Si6B 14 Y2, the actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was 7.197 g / cm 3 .

[0053] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 78 Si6B 14 Y2 was crushed into single alloy particles of 2-3g. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt-spinning machine. The vacuum degree in the furnace chamber was pumped to 4.0×10 -3 Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1400℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain the alloy strip, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 78 Si6B 14The thickness of the Y2 multi-principal amorphous alloy strip is 30±8 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 40 m / s.

[0054] Example 4

[0055] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0056] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) are selected as raw materials, the oxide scale is polished and then ultrasonically cleaned with acetone or alcohol, and a high-precision balance with an accuracy of 0.001g is used for mixing the ingredients, wherein 8.534g of iron particles, 9.005g of cobalt particles, 8.969g of nickel particles, 1.003g of silicon fragments, 0.901g of boron fragments and 1.588g of yttrium blocks are used.

[0057] (2) Repeat the vacuum three times until the pressure in the furnace reaches 4.5×10 -3 Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 230A for 5 minutes, and a master alloy ingot is prepared by an arc smelting method to complete one smelting. During the smelting, cooling water is passed to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 4 times for a total of 20 minutes to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 77 Si6B 14 Y3, the actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was 7.157 g / cm 3 .

[0058] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 77 Si6B 14 Y3 was crushed into single alloy particles of 2-3g. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt-spinning machine. The vacuum degree in the furnace chamber was pumped to 4.0×10 -3Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1400℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain the alloy strip, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 77 Si6B 14 The thickness of the Y3 multi-principal amorphous alloy strip is 30±8 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 40 m / s.

[0059] Example 5

[0060] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0061] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) are selected as raw materials, the oxide scale is polished and then ultrasonically cleaned with acetone or alcohol, and the ingredients are mixed using a high-precision balance with an accuracy of 0.001g, wherein 8.371g of iron particles, 8.834g of cobalt particles, 8.798g of nickel particles, 0.997g of silicon fragments, 0.896g of boron fragments and 2.104g of yttrium blocks are mixed.

[0062] (2) Repeat the vacuum three times until the pressure in the furnace reaches 4.5×10 -3 Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 230A for 5 minutes to prepare a master alloy ingot by arc smelting. During the smelting, cooling water is passed to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 4 times to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 76 Si6B 14 Y4, the actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was 7.003 g / cm 3 .

[0063] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 76 Si6B14 Y4 was crushed into single alloy particles of 2-3g. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt-spinning machine. The vacuum degree in the furnace chamber was pumped to 4.0×10 -3 Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1400℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain the alloy strip, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 76 Si6B 14 The thickness of the Y4 multi-principal amorphous alloy strip is 30±8 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 40 m / s.

[0064] Example 6

[0065] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0066] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) were selected as raw materials, and after grinding the oxide skin, ultrasonic cleaning was performed with acetone or alcohol. The cleaning agent was acetone, and the number of cleanings was 3 times. A high-precision balance with an accuracy of 0.001g was used for mixing the ingredients, wherein 8.865g of iron particles, 9.355g of cobalt particles, 9.317g of nickel particles, 1.016g of silicon fragments, 0.912g of boron fragments and 0.536g of yttrium blocks were used.

[0067] (2) Repeat the vacuum three times until the pressure in the furnace reaches 4×10 -3 Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 250A for 4 minutes to prepare a master alloy ingot by arc smelting. During the smelting, cooling water is used to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 5 times for a total of 20 minutes to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 Y1, the actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was 7.289 g / cm 3 .

[0068] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 Y1 was crushed into single alloy particles of 2-3g. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt-spinning machine. The vacuum degree in the furnace chamber was pumped to 5.0×10 -3 Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1300℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain alloy strips, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 The thickness of the Y1 multi-principal amorphous alloy strip is 30±5 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 25 m / s.

[0069] Example 7

[0070] This embodiment provides a method for preparing a FeCoNi-based amorphous alloy, and the specific steps and parameters are as follows:

[0071] (1) High-purity iron particles, cobalt particles, nickel particles, boron fragments, silicon fragments and yttrium blocks (with a purity of not less than 99.9%) were selected as raw materials, and after grinding the oxide skin, ultrasonic cleaning was performed with acetone or alcohol. The cleaning agent was acetone, and the number of cleanings was 3 times. A high-precision balance with an accuracy of 0.001g was used for mixing the ingredients, wherein 8.865g of iron particles, 9.355g of cobalt particles, 9.317g of nickel particles, 1.016g of silicon fragments, 0.912g of boron fragments and 0.536g of yttrium blocks were used.

[0072] (2) Repeat the vacuum three times until the pressure in the furnace reaches 5×10 -3 Pa, then high-purity argon gas with a purity of 99.999% is introduced until the vacuum chamber pressure is -0.8MPa, and the remaining impurity gas is adsorbed by sponge titanium. After the gas adsorption is completed, under vacuum and argon protection conditions, the raw materials weighed in step (1) are smelted at a smelting current of 180A for 7 minutes to prepare a master alloy ingot by arc smelting. During the smelting, cooling water is used to prevent the water-cooled copper plate from overheating and melting. The smelting step is repeated 3 times for a total of 21 minutes to ensure the uniformity of the composition of the alloy ingot. After cooling, a master alloy ingot is obtained. The chemical formula of the master alloy ingot is (Fe 1 / 3 Co1 / 3 Ni 1 / 3 ) 79 Si6B 14 Y1, the actual density of the alloy was measured by the displacement method using a Sartorius electronic analytical balance and was 7.289 g / cm 3 .

[0073] (3) The master alloy ingot (Fe) obtained by smelting in step (2) 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 Y1 was crushed into single alloy particles of 2-3g. 3g of the crushed master alloy ingot was placed in a quartz tube. The quartz tube was placed in the induction coil of the belt-spinning machine. The vacuum degree in the furnace chamber was pumped to 5.0×10 -3 Pa, then filled with argon, repeated vacuum operation to ensure that there is no impurity gas in the furnace chamber, and adjusted the pressure difference between the inside and outside of the quartz tube to 0.02MPa, heated the master alloy ingot to 1500℃ through the copper coil, and after the alloy was melted, the liquid alloy was sprayed onto the high-speed moving copper roller to obtain the alloy strip, (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79 Si6B 14 The thickness of the Y1 multi-principal amorphous alloy strip is 34±6 μm, wherein the diameter of the quartz tube nozzle is 0.8 mm, the height of the nozzle from the copper roller is 0.4 mm, and the surface linear speed of the copper roller is 30 m / s.

[0074] Experimental Example 1

[0075] The phase analysis of the multi-principal amorphous alloy strips of Examples 1-5 was performed using a Japanese Rigaku Smart lab (9kw) X-ray diffractometer. The operating voltage and current were 45kV and 40mA, respectively. The X-ray source was Cu Kα (λ=0.15406nm) rays. The scanning speed was 2° / min, and the scanning range was 30°~80°. The results are shown in Figure 1 , it can be seen that, except for (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 79.5 Si6B 14 Y 0.5 The alloy presents an amorphous structure and Fe 4.5 Ni 18.5 Except for the two-phase structure of the B6 crystallized phase, the other four multi-principal amorphous alloys have typical diffuse scattering peaks of amorphous structure, indicating that the prepared strips do have an amorphous structure.

[0076] The microstructure morphology of the surface of the multi-principal amorphous alloy strips of Examples 1-5 was characterized using a German ZEISS GeminiSEM300 scanning electron microscope. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the surface of the multi-principal amorphous alloy strip is smooth, flat and dense, the structure is uniform, and there are no obvious holes on the surface of the strip, indicating that the prepared alloy strip is of good quality.

[0077] Experimental Example 2

[0078] The thermal stability of the multi-principal amorphous alloys prepared in Examples 1-5 and the common soft magnetic amorphous alloy materials on the market were tested using a differential scanning calorimeter (DSC404-F3 model) produced by NETZSCH, Germany.

[0079] Table 1 Thermal stability properties of multi-principal amorphous alloy strips

[0080]

[0081] according to Figure 3 As shown in Table 1, the first initial crystallization temperature Tx1 of the multi-principal amorphous alloy provided by the present invention is above 695K, indicating that when working below this temperature, the material can maintain an amorphous structure and meet the requirements of use in high-temperature service environments. 83.3 Si4B8P4Cu 0.7 The first starting crystallization temperature T x1 is 689K, which is lower than the T of the amorphous alloy developed by the present invention. x1 value, so the alloy involved in the present invention has better thermal stability.

[0082] Experimental Example 3

[0083] The hardness of the multi-principal amorphous alloys obtained in Examples 1-5 and Comparative Examples 1-2 was tested using a HVS-1000A digital display automatic turret micro-Vickers hardness tester. The results are as follows: Figure 4 As shown, the Vickers hardness of the multi-principal amorphous alloys prepared in Examples 1-5 is in the range of 753-782 HV 0.5 Compared with the traditional and common Al-based amorphous alloy strips of the same thickness, the multi-principal amorphous alloy material provided by the present invention has a higher hardness, and the microhardness is about 3 times that of the conventional and common Al-based amorphous alloy strips of the same thickness. 86 The hardness of Ni6Y6Ce2 amorphous alloy ribbon is 252HV 0.1 , Al 86 7Y 4.5 Co1La 1.5 The hardness of amorphous alloy ribbon is 271HV 0.1 ).

[0084] Experimental Example 4

[0085] A vibrating sample magnetometer (VSM, equipment model: LakeShore7404) was used to test the hysteresis loops of the multi-principal amorphous alloys of Examples 1-5 to obtain the saturation magnetization of the samples, and the mass of each test sample was about 4 mg. Since VSM cannot accurately measure the coercivity of Fe-based amorphous soft magnetic alloys, a BHS-40 DC BH hysteresis loop instrument was used to measure the coercivity of soft magnetic amorphous alloy strips.

[0086] The test strip sample size is 60-70 mm in length, 30-50 μm in thickness, and 1-2 mm in width. Figure 5-Figure 6 shown.

[0087] from Figure 5-Figure 6 It can be seen that the saturation magnetic induction intensity M of the multi-principal amorphous alloys prepared in Examples 1 to 5 is s At 83.5emu / g~104.3emu / g, coercivity H c The saturation magnetic induction intensity M is 12.2A / m~26.7A / m. Compared with CoCrFeNiCuAl multi-element alloy, its saturation magnetic induction intensity M s It is only 38.18emu / g (Journal of Alloys and Compounds 502(2)(2010):295-299.), which is much lower than the multi-principal amorphous alloy designed by the present invention. At the same time, it can be found that with the increase of the Y element content, the magnetic induction intensity M of the multi-principal amorphous alloy prepared by the embodiment of the present invention increases. s Gradually decreases, coercivity H c The alloy materials provided by the present invention are all typical soft magnetic amorphous alloy materials, with a coercive force of less than 1000A / m and good soft magnetic properties.

[0088] Experimental Example 5

[0089] The corrosion resistance of Examples 1-5, Comparative Examples 1-2 and commonly used marine engineering steels (45 steel, F22 heat-resistant ferrite synthetic steel, LA141 magnesium alloy and T10) was tested using a Shanghai Chenhua 660E electrochemical workstation (test method references ①Cheng JB, Feng Y, Yan C, et al. Development and Characterization of Al-Based Amorphous Coating[J]. JOM, 2020, 72(3), 745-753. ②Zhang BS, Dong QS, Ba ZX, et al, Electrochemical corrosion behavior of plasma-sprayed FeCrNiMoCBSiamorphous / nanocrystalline coatings in Simulated seawater Medium, J. Mater. Eng. Perform. 27(2018) 6227-6236. ③Sun YJ, Yang R, Xie L, et al., Interfacial bonding mechanism and properties of HVOF-sprayed Fe-based amorphous coatings on LA141 magnesium alloy substrate, Surf. Coating. Technol. 426 (2021) 127801.) The corrosion solution is a 3.5wt.% NaCl solution simulating the concentration of marine salt. The results are shown in Figure 7 and Table 2.

[0090] Table 2 Alloy corrosion parameters

[0091]

[0092]

[0093] “ / ” in the table means that the value cannot be determined or is not provided in the literature.

[0094] In Table 2, the self-corrosion current density represents the actual corrosion rate. The smaller the corrosion current density, the lower the corrosion degree under the same conditions. The corrosion potential represents the corrosion tendency. The higher the self-corrosion potential under the same conditions, the lower the corrosion tendency. The larger the polarization resistance, the less likely the material is to corrode. It should be pointed out that when evaluating the quality of a material, various parameters should be considered comprehensively. Among them, the corrosion current density can mainly indicate the corrosion resistance of the material. The smaller the corrosion rate, the better the corrosion resistance of the material.

[0095] according to Figure 7 As shown in Table 2, the corrosion potentials of the multi-principal amorphous alloys containing rare earth element Y are not much different, but are higher than those of common metal materials such as 45 steel, LA141 magnesium alloy and T10 steel. The corrosion current density of the multi-principal amorphous alloys prepared in Examples 1-5 is between 1.452 and 3.017 μA·cm -2 , and the chemical formula obtained in Example 5 is (Fe 1 / 3 Co 1 / 3 Ni 1 / 3 ) 76 Si6B 14 The corrosion current density of the Y4 multi-principal amorphous alloy is the smallest, and the polarization resistance is also the largest, so its corrosion resistance is the best. This also further illustrates that the multi-principal amorphous alloy material provided by the present application has a lower corrosion tendency and a smaller actual corrosion rate than existing common steel materials in the corrosive environment of 3.5wt% NaCl solution, and therefore has a better corrosion resistance.

[0096] In summary, the multi-principal amorphous alloy provided by the present invention not only has good soft magnetic properties, but can also be used as a core material for offshore wind turbines. Moreover, this type of material can also have excellent corrosion resistance and thermal stability; at the same time, compared with aluminum-based amorphous alloys, it also has the characteristics of high hardness, so that it can be applied to marine environment materials that need to have corrosion resistance, high thermal stability and high hardness. However, it should be pointed out that due to the limitations of the preparation process of multi-principal amorphous alloys, the output cannot be too large, so it is often used as a raw material for surface protective coatings of ships or large marine equipment, which can improve the hardness of steel and surface corrosion resistance, and will not lose the original magnetic performance characteristics, without the need to replace its raw materials on a large scale, and will not produce chemical pollution caused by anti-corrosion coatings. The required raw materials are all common raw materials in the field, the operation steps are simple and easy, the process is easy to control, and it is possible to obtain amorphous soft magnetic alloys with uniform composition and all performances can be taken into account.

[0097] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A FeCoNi-based amorphous alloy, characterized in that: The chemical formula of the FeCoNi-based amorphous alloy is (Fe 1 / 3Co 1 / 3 Ni 1 / 3 ) 80-x Si6B 14 Y x , where the value of x ranges from 0.5 to 4.

2. The FeCoNi-based amorphous alloy according to claim 1, characterized in that: The value range of x is 1-4.

3. The FeCoNi-based amorphous alloy according to claim 2, characterized in that: The amorphous alloy has a thickness of 25-50 μm and a width of 1-2 mm.

4. A method for preparing a FeCoNi-based amorphous alloy according to any one of claims 1 to 3, characterized in that: The steps include: Mixing iron, cobalt, nickel, silicon, boron and yttrium according to a ratio to obtain a mixture; In an inert atmosphere, the mixed material is melted to obtain an intermediate; The intermediate is quenched in an inert atmosphere to obtain the amorphous alloy.

5. The method for preparing a FeCoNi-based amorphous alloy according to claim 4, characterized in that: The smelting method includes at least one of induction melting or arc melting; and / or, The mixed material is smelted at least 3 times, preferably 3-5 times; and / or, The temperature during quenching is 1300-1500°C, and the cooling rate during quenching is greater than or equal to 10 5 K / s.

6. The method for preparing a FeCoNi-based amorphous alloy according to claim 5, characterized in that: The vacuum degree of the smelting is 4.0×10 -3 Pa~5.0×10 -3 Pa; and / or, In the arc melting process, the melting current is 180-250A, and the single melting time is 4-7 minutes.

7. The method for preparing a FeCoNi-based amorphous alloy according to claim 6, characterized in that: The intermediate is quenched by melting with an induction coil; and / or, The cooling step includes spraying the molten alloy liquid onto the surface of the metal roller, and the surface linear speed of the metal roller is 25-40m / s.

8. The method for preparing a FeCoNi-based amorphous alloy according to any one of claims 4 to 7, characterized in that: The atomic ratio of iron, cobalt, nickel, silicon, boron and yttrium is 25-27:25-27:25-27:6:14:0.5-4.

9. The method for preparing a FeCoNi-based amorphous alloy according to claim 8, characterized in that: Before mixing the iron, cobalt, nickel, silicon, boron and yttrium, the process also includes polishing and cleaning the surfaces of the raw materials. The cleaning includes ultrasonic treatment, the cleaning agent is acetone or ethanol, and the number of cleaning times is 1-3 times.

10. Application of the FeCoNi-based amorphous alloy according to any one of claims 1 to 3 or the amorphous alloy prepared by the preparation method of the FeCoNi-based amorphous alloy according to any one of claims 4 to 9 in metal structural parts, magnetic core materials and protective coatings in marine engineering.